Communication Management In Self Healing Health Services - Dwiwarman, Denny Aditya; Andriani, Astri Dwi; Suryati, Enden; Hilmawan, Irfan Sophan; Djuarni, Wenny; Teguh, Dodi Faraitody; Kartini, Iis; Jamilah, Pupu; Nurlaela, Reni; Agustinah, Aminah; Sulaeman, Pradika (Aspiration of Health Journal, 2024)
Currently, self-healing is an alternative for patients who want to undergo treatment outside the standard medical treatment and want to reduce the negative impact of drug side effects. Self-healing is a method of healing diseases without using drugs, but by healing and releasing feelings and emotions that are pent up in the body. In carrying out its services, the Hanara Wellbeing Center Clinic uses the principle of therapeutic communication in serving patients. This phenomenon is then studied using the construction paradigm, qualitative methods, case study approaches, and social construction theory. The data collection techniques used were participant observation for one year, interviews with 6 key informants and triangulation of 19 sources, literature studies, and document studies. The data analysis technique used the Miles and Huberman interactive model and validity testing used data triangulation. The results of the study showed that the Hanara Wellbeing Center Clinic uses 2 types of therapeutic communication in serving patient self-healing, namely verbal therapeutic communication consisting of words and language. And nonverbal communication consisting of kinesics, paralinguistics, proxemics, chronemics, artifactual communication, and using artifacts or healing environments. All of these communication components are used to make patients feel comfortable, safe, calm, and happy so that the healing process can be accelerated.